(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article deals with teaching English to preschool children, conducting the lesson process with ecological examples, and organizing lessons using the total physical method. Also, a program for conducting environmental-English language classes is recommended